Desain Bangunan Multifungsi: Pasar dan Fasilitas Umum di Kabupaten Semarang - Riza Susanti; Previari Umi Pramesti; Shifa Fauziyah (Jurnal Pengabdian Vokasi, 2022)
Traditional Market is a place to carry out trading activities related basic necessities that cannot be separated from human daily activities. Unfortunately, the layout of traditional market is often inconsistent in its arrangement. This causes the traditional market to seem chaotic. However, the urgency of the existence of a market in an area is important to accommodate the fulfillment of community needs. The problem faced, there is one sub-district in Semarang Regency which still does not have a market. In addition, there is a need for public facilities to optimize the role of youth organizations in the area. The purpose of this service activity is to facilitate by providing assistance in building planning that can accommodate these needs. The method used is observation followed by making design based on the needs. The result of this activity is design of a multifunctional building which is expected to be used as a comfortable market as well as public facilities such as an area for futsal. The multifunctional building which will later be called the JATIBARANG SQUARE MARKET is estimated to have a Budget Plan (RAB) of Rp. 165,695,638,925,-